Semantic-syntactic structure of subjectless sentences with verbal predicates of condition (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2016)
The article analyzes the semantic and syntactic structure of ssubjectless sentences of verbal predicates condition; identified the main structural diagrams and models of types such sentences, conducted distributive analysis of verbal predicates subjectless condition, defined types of semantics sentences generated by these predicates.Is noted that the sentence subjectless state formed on the basis of predicates distributional properties of which do not provide for the mandatory implementation of subject and object syntaxemes. Considering the generalization of the scientific viewpoint determined that, firstly, the main feature of grammatical sentences with these predicates is impersonality. Second, on the basis of this type of predicates are formed elementary sentence that in traditional syntax called impersonal. It was found that the model PraedstVf presented by sentences formed on the basis of verb's predicate to denote «a comprehensive» state of the external environment. Verbal predicates a comprehensive state are limited group and denote conditions created by natural forces. In Ukrainian linguistics, they are regarded as syntactic variant of monovalent verbs. Proved that subjectless sentence in Ukrainian language form only verbal predicates to denote the environment; submitted semantic differentiation of predicates. Defined the structural types of model of subjectless sentences of verbal state, default and optional redistributors. Indicated that sentence with verbal predicates subjectless condition include optional temporal distribution, causative, for qualitative adverbialnymy and other components. The structural model types subjectless sentences of verbal state, default and elective redistributors. Indicated that sentence with subjectless verbal predicates of state include an optional spread by temporal, causative, qualitative and other adverbialnymy components.
Keywords: semantic-syntactic relations; subjectless sentence; verbal predicate condition; structural condition; complement